2016
DOI: 10.1038/srep33722
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake mechanism and germination of Erythrina velutina seeds treated with atmospheric plasma

Abstract: The effect of plasma applied to mulungu (Erythrina velutina) seeds was studied to verify its influence on the germination, water absorption, wettability and structure of the seeds. The plasma jet used in this study was produced by dielectric barrier discharge (DBD) in a helium gas flow of 0.03 L/s at a distance of 13 mm for 60 s. The plasma treatment significantly affected the seed germination rate, which was approximately 5% higher than that of the untreated group. Micropyle and hilum contributed a greater pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 18 publications
2
42
3
2
Order By: Relevance
“…The early stage of water uptake into seeds is the crucial period for seed germination. Previous studies have indicated that a plasmainduced improvement in seed germination was related to the water uptake of seeds [27,28]. In this study, cold plasma treatment markedly increased the water uptake of oilseed rape seed (figure 4).…”
Section: Discussionsupporting
confidence: 56%
“…The early stage of water uptake into seeds is the crucial period for seed germination. Previous studies have indicated that a plasmainduced improvement in seed germination was related to the water uptake of seeds [27,28]. In this study, cold plasma treatment markedly increased the water uptake of oilseed rape seed (figure 4).…”
Section: Discussionsupporting
confidence: 56%
“…These processes occur through the adsorption of the functional groups originated from the interaction between free radicals produced by plasma and the constituent elements of the integument. This way, there is increased absorption of water by the seeds (LING et al, 2014;BORMASHENKO et al, 2015;ZAHORANOVA et al, 2016;ALVES JÚNIOR. et al, 2016b;SIVACHANDIRAN;KHACEF, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that discharge plasma can increase the germination, growth and yield of various plant seeds such as pea, wheat, tomato and Andrographis paniculata [14][15][16][17], it can improve the hydrophilicity of the surface of soybean seeds, thereby increasing the germination speed of seeds [18], it etches the wheat seed coat, which leads to an increase in water absorption capacity [19], it can reduce the apparent contact angle of Erythrina velutina (mulungu) seeds and change the hydrophilicity of seeds [20]. The interaction between HVEF and an organism is very complex, in order to explore the role and contribution rate of the two factors in HVEF, when naked oat seeds were treated, one group was exposed directly, the other group was covered with a petri dish cover (blocking the influence of ion wind, the result can be approximated by the electric field single factor effect).…”
Section: Introductionmentioning
confidence: 99%